2017
DOI: 10.1002/aenm.201702365
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Bias Behavior of Halide Perovskite Solar Cells

Abstract: solar cells have a breakdown voltage (V BD ) at which current starts to flow in reverse bias. When current flows in reverse bias, the shaded cell dissipates power rather than producing it, and this can cause local heating, which damages the cell. [8] Silicon cells generally breakdown in reverse bias by avalanche breakdown; the carriers gain enough kinetic energy from the applied electric field to generate additional carriers through impact ionization. V BD s for silicon cells are typically >15 V. If the pn jun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
206
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(215 citation statements)
references
References 33 publications
9
206
0
Order By: Relevance
“…1 Although light-to-power conversion efficiencies have rapidly increased to a certified record of 24.2% 2 (B0.1 cm 2 , initial efficiency), perovskite solar cells still suffer from relatively poor operational stability compared to commercial photovoltaic technologies. 3,4 It is well documented that extrinsic parameters such as moisture, 5 oxygen, 6 light, 7 temperature, 8 electric fields, 9 reverse bias, 10 strain, 11 etc. strongly influence the stability of perovskite solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…1 Although light-to-power conversion efficiencies have rapidly increased to a certified record of 24.2% 2 (B0.1 cm 2 , initial efficiency), perovskite solar cells still suffer from relatively poor operational stability compared to commercial photovoltaic technologies. 3,4 It is well documented that extrinsic parameters such as moisture, 5 oxygen, 6 light, 7 temperature, 8 electric fields, 9 reverse bias, 10 strain, 11 etc. strongly influence the stability of perovskite solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…Heterogeneous illumination presents a serious issue, as shaded regions of a single solar cell experience reverse bias, in contrast to other areas in the device that are under illumination. 68,69 Concerning light treatments, the substantial variety of possible illumination conditions must be emulated at the laboratory scale first in order for the ML analysis to perform well in real-world situations.…”
Section: To Identify and Optimize Device Recoverymentioning
confidence: 99%
“…As a result, the accumulated charges at the interfaces lead to the formation of radicals and the observation of hysteresis in IV curves. Moreover, the induced external ion diffusion into the transporting layers and metal contacts provoke the formation of carrier traps and detrimental reactions [22][23][24]. In particular, it is reported that a reverse bias voltage of merely −1 to −4 V can cause the breakdown of perovskite solar cells, while the breakdown value for silicon solar cells is around −15 V [24].…”
Section: Single Stress Factorsmentioning
confidence: 99%
“…Moreover, the induced external ion diffusion into the transporting layers and metal contacts provoke the formation of carrier traps and detrimental reactions [22][23][24]. In particular, it is reported that a reverse bias voltage of merely −1 to −4 V can cause the breakdown of perovskite solar cells, while the breakdown value for silicon solar cells is around −15 V [24]. The mechanism is considered to be the shunt path formation or the electrochemical reaction of defects in the contacts [24].…”
Section: Single Stress Factorsmentioning
confidence: 99%
See 1 more Smart Citation